Influence of gender on choice of undergraduate degree programmes A case of students at Great Zimbabwe University. (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
The choice of a college degree program can be one of the most important decisions a student can make. This paper investigated the influence of gender on the choice of degree programmes at Great Zimbabwe University.  Data was collected from a sample of 37 students from 3 faculties through a questionnaire. We also used data from the graduands of the 6th Graduation Ceremony , October 2012 at Great Zimbabwe University. The analysis revealed that gender plays a part in the choice of degree programmes. This is attributed to a variety of factors which include the fact that society is patriarchal where women feel insecure to venture into challenging programmes. We recommend researchers to investigate further into this issue for the sake of generalisation.